Breaking into Japanese Literature/Identity: Tatemae and Honne - Ishii, Tetsuo; Saravia Vargas, José Roberto; Saravia Vargas, Juan Carlos (Impossibilia. Revista Internacional de Estudios Literarios, 2011)
Due to the application of Euro-centered methods of interpretation, literary criticism has overlooked key social aspects that are characteristic of Japanese literature. Among these much-neglected characteristics one can include the paired concepts tatemae and honne. By incorporating those concepts into a reading of Japanese texts, the reader can discover social issues previously unseen. Banana Yosimoto’s novel Kitchen is used to illustrate the different interactions of tatemae and honne.